ARTIFICIAL ENVIRONMENT FOR ENGLISH COMMUNICATION “CASE STUDY AT ONE OF BILINGUAL ISLAMIC BOARDING SCHOOL IN PROBOLINGGO” - Himmatul Maula; Mamluatun Ni’mah; Shofiyatul Hasanah (STKIP PGRI Situbondo, 2023)
The built environment with the aim of mastering English with a communicative approach is indeed often applied in the educational environment of Islamic boarding schools or bilingual schools or boarding-based educational institutions. This is to form students who are capable and master foreign languages ​​needed for preparation for entering college and preparation for work. The purpose of this research is to find out the application of an artificial environment in one of the bilingual islamic boarding schools in Probolinggo, in communicating using English. This research uses descriptive methods with a qualitative approach including primary data, namely data taken from interviews, observation, and documentation and secondary data, namely data collected from various previous studies in scientific articles, relevant books, and other research. , to internet sites that have a relationship with this research . The results found that there was success in implementing an artificial environment for English communication in one of the bilingual Islamic boarding schools in Probolinggo. This is seen through the mental or social processing carried out by students in empirical institutions. First, a communication strategy by selecting communicators or English teachers who are truly competent in their fields. Second, using a mapping strategy for students of various levels to hone their communication competence in English. Third, the challenge faced by students is listening to foreign vocabulary that is difficult for them to understand. Fourth, the implementation of the environment in this pesantren shows maximum value even though there are some students who are reluctant to communicate in English because of awareness and lack of pressure from parents. Fifth, the symbolic result of mandatory English communication is the way students joke, mingle, socialize, and learning activities in the cottage using English